Privatizing or Socializing Corporate Responsibility: Business Participation in Voluntary Programs. (July 2014) - Fransen, Luc; Burgoon, Brian
This article explores why companies choose some Corporate Responsibility initiatives over others. The focus is on competing voluntary programs to oversee and protect labor standards. These programs may differ with regard to two aspects: the governance of the program and the financial and managerial responsibility for compliance. These aspects are crucial to distinguish "socializing" or "privatizing" types of voluntary labor regulation. The article explores the conditions under which companies in apparel production choose different types of governance and responsibility, based on qualitative and quantitative evidence of the European industry. The study shows that corporate preference for multi-stakeholder governed programs is positively affected by societal pressure orchestrated by NGOs, through both public campaigns and informal efforts, together with pressures from consumers and media. Second, the position of the firm in the value chain affects preference for taking financial and managerial responsibility for compliance.